Case Report: Vesicouterine fistula following vaginal delivery - Zeinab Khademi; Mahnaz Boroumand Rezazadeh; Farhad Yousefi; Fahimeh Alizadeh (Mashhad University of Medical Sciences, 2019)
Introduction: Various maternal obstetrical complications may occur following each type of delivery. One of these rare but important and problematic complications is orogenital fistula. The incidence of different types of orogenital fistula following delivery is more common in cesarean section and only few cases have been reported following normal vaginal delivery. In this article, a case of vesicouterine fistula after normal vagina delivery is reported. Case presentation: The patient was a 31-year-old woman with third pregnancy and history of two previous normal vaginal deliveries without complication who had referred to the emergency ward of Mashhad Imam Reza hospital because of labor pain at gestational age of 38 weeks. Delivery progressed from the initial dilation 5 cm and effacement 60% within 2 hours of admission by spontaneous contractions. After delivery of head and shoulders, dystocia occurred during expulsion of abdomen due to large palpable abdominal mass in the fetus; and delivery was done with difficultly. Approximately 10 days after delivery, the patient referred with complaint of malodor watery discharge from vagina. After performing the methylene blue test, diagnosis of the vesicouterine fistula was confirmed by cystography. Urinary foley catheterization was inserted for the patient for 3 months and after re-performing cystography, vesicouterine fistula was completely repaired without need to surgery. Conclusion: Vesicouterine fistula is of the rarest types of urogenital fistula which is often occurred following cesarean section and sometimes after normal vaginal delivery. One of the risk factors of vesicouterine fistula following vaginal delivery is "labor dystocia". Many cases of vesicouterine fistula are treated by conservative management and surgery is not needed.